Extension Of Numerical Manifold Method For Plasticity And Fracture Modelling Of Rock Mass - Bateni, Farshid (2014)
Previous studies on numerical modelling of geotechnical engineering problems indicate the importance of modelling in safe and sustainable designing of geotechnical projects. Generally, the stability of built engineering structures in rock is directly influenced by stability of the rock mass that contains the structure. In addition, the economical engineering design usually suggests the usage of existing rock to support the underground structure hence minimizing the additional handling of support systems. Therefore, an accurate and precise assessment of rock stability is required, that can be hugely achieved by modelling the rock mass stability. However, many approximations considered in the traditional modelling techniques of the rock mass were not able to simulate both discontinuity and continuum problems. Hence, new models have been developed and improved for providing accurate modelling techniques for rock mechanics. The Numerical Manifold Method (NMM) developed by Shi (1997) is one of the hybrid continuum–discontinuum models which is suitable for modelling complex problems in rock mechanics. However, the NMM method requires extension for solving the plasticity and cracking problems to model rock mass stability and determines reliable simulation results.